Cost-effectiveness of the use of low- and high-potency statins in people at low cardiovascular risk - Conly, Jon (Canadian Medical Association, 2011)
BACKGROUND: Although statins have been shown to reduce the risk of cardiovascular events in patients at low cardiovascular risk, their absolute benefit is small in the short term, which may adversely affect cost-effectiveness. We sought to determine the long-term cost-effectiveness (beyond the duration of clinical trials) of low- and high-potency statins in patients at low cardiovascular risk and to estimate the impact on Canada’s publicly funded health care system. METHODS: Using Markov modelling, we performed a cost-utility analysis in which we compared low-potency statins (fluvastatin, lovastatin, pravastatin and simvastatin) and high-potency statins (atorvastatin and rosuvastatin) with no statins in a simulated cohort of low-risk patients over a lifetime horizon. Model outcomes included costs (in 2010 Canadian dollars), quality-adjusted life-years (QALYs) gained and the cost per QALY gained. RESULTS: Over a lifetime horizon, the cost of managing a patient at low cardiovascular risk was estimated to be about $10 100 without statins, $15 200 with low-potency statins and $16 400 with high-potency statins. The cost per QALY gained with high-potency statins (v. no statins) was $21 300; the use of low-potency statins was not considered economically attractive. These results were robust to sensitivity analyses, although their use became economically unattractive when the duration of benefit from statin use was assumed to be less than 10 years. INTERPRETATION: Use of high-potency statins in patients at low cardiovascular risk was associated with a cost per QALY gained that was economically attractive by current standards, assuming that the benefit from statin use would continue for at least 10 years. However, the overall expenditure on statins would be substantial, and the ramifications of this practice should be carefully considered by policy-makers.